2022
DOI: 10.1109/jphot.2022.3187417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Transverse Mode Instability Characteristics of Few-Mode Fiber Laser Amplifier Under Different Bending Conditions

Abstract: We studied the transverse mode instability (TMI) characteristics of few-mode fiber laser amplifier employing ytterbium-doped fiber (YDF) with core/cladding diameter of 30/400μm under different bending diameters. The gain fiber is coiled in ellipse shape with minimum bending diameter changed from 9cm, 10cm, 11cm to 12cm in the bending part, and the experimental results show an anomaly characteristic of TMI. The TMI threshold improved from 772W, 1149W and 1458W to 1641W when the bending diameter of YDF increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, we found the abnormal TMI suppression method that the TMI threshold increases with the increase of coiling diameter. In [72], we realized the fiber laser amplifier with 30/400 µm fiber, and found that when the minimum coiling diameter of the fiber gradually increased from 9 cm to 12 cm, the TMI threshold of the laser gradually increased. Subsequently, we design a high-power fiber laser amplifier based on the double-cladding YDF with a core/cladding diameter of 30/600 µm.…”
Section: Abnormal Tmi Suppression Methods Based On Fiber Coilingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found the abnormal TMI suppression method that the TMI threshold increases with the increase of coiling diameter. In [72], we realized the fiber laser amplifier with 30/400 µm fiber, and found that when the minimum coiling diameter of the fiber gradually increased from 9 cm to 12 cm, the TMI threshold of the laser gradually increased. Subsequently, we design a high-power fiber laser amplifier based on the double-cladding YDF with a core/cladding diameter of 30/600 µm.…”
Section: Abnormal Tmi Suppression Methods Based On Fiber Coilingmentioning
confidence: 99%
“…In recent years, with the goal of achieving a high-power fiber laser with high beam quality, we have been focusing on balancing SRS and TMI by optimizing the pump wavelengths and pump configuration. In the aspect of fiber coiling, we found the abnormal phenomenon of increasing the TMI threshold by increasing the fiber coiling diameter [10,72]. In addition, we propose varying core diameter active fiber represented by tapered fiber, spindle-shaped fiber, and saddle-shaped fiber, which can balance SRS and TMI in the fiber and break through the power limit of conventional fiber [73][74][75][76][77][78][79][80][81].…”
Section: Introductionmentioning
confidence: 93%
“…The length of the YDF of amplifier stage is about 23 m. The YDF was coiled with a minimum radius of 12 cm and a maximum radius of 16 cm in the grooves on a water-cooled heat sink. The selection of coiling radius is to balance TMI threshold and beam quality [24]. When bending diameter is larger than 12 cm, the MI threshold would be improved with deterioration of beam quality; with smaller coiling radius, the beam quality could maintain well but the MI threshold would decrease.…”
Section: Experimental Design and Setupmentioning
confidence: 99%
“…So far, SRS and TMI have become the main factors limiting the power increase of high-power fiber lasers, and there is a sharp contradiction in their suppression methods [ 35 , 36 ]. Researchers have conducted extensive theoretical and experimental research on the suppression of SRS and TMI, including active fiber, signal wavelength, pump wavelength, pump configuration, pump modulation, and fiber coiling [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. With the support of the above suppression measures, the output power of fiber lasers has achieved great breakthroughs.…”
Section: Introductionmentioning
confidence: 99%